The AI Decision-Making Schema: Controlling the Golem - Jacek ENGEL; Dariusz RAŚ; Anna PRUSAK (Communications of International Proceedings, 2024)
The present paper has a review and conceptual nature. The initial assumption situates the controversy around AI within decision-making processes. According to the authors, decision-making power (or decisiveness) is the factor that should determine the use of this technology. Therefore, the considerations presented here are not only about the essence of AI in the context of sophisticated algorithms, but also about decision-making as an inherent attribute of humans, entire civilizations and economies. Historical and contemporary methods of decision support systems are reviewed, including advanced technologies such as supercomputers. Finally, the authors’ concept called the “Golem Button” is presented, which aims to provide managers and legislators with a tool to structure standards and guidelines on how artificial intelligence systems (contemporary and future) can be used safely in different areas of the economy.
Keywords: AI; decision-making; autonomy; algorithms; golem.